Factors Associated with Stock Price Volatility and Evaluation of Gordon's Share Valuation Model on the Kuala Lumpur Stock Exchange - Mohamad, Shamsher; Md Nassir, Annuar (Universiti Putra Malaysia Press, 1993)
The worldwide increase in share price volatility in recent years has stimulated an abundance of research in an effort to understand individual share price volatility in international markets. The objectives of this study are: (i) to isolate factors suggested by investment theories and practices and to observe their ability to jointly explain share price volatility on the developing Kuala Lumpur Stock Exchange (KLSE) and (ii) to evaluate the applicability of Gordon's share valuation model on the KLSE. The findings suggest that five of the six suggested variables jointly explain 23 per cent of price changes on the KLSE for the period 1975 to 1990, and two of these factors were significant at 5 per cent level. Gordon's model holds well with F-statistics significant at 5 per cent level, R-squared is 70 per cent, and the signs of the coefficient of dividend and earnings growth variables are in the predicted direction. Contrary to popular belief, fundamental factors appear to be a significant force influencing share price changes on the KLSE.